Value of the QRS-Selvester scoring in the acute myocardial infarction - Francisco de Jesús Valladares Carvajal; Frank Carlos Álvarez Li; Marcos Diosdado Iraola Ferrer; Rosendo Ibargollín Hernández (ECIMED, 2014)
74 patients with diagnosis of acute myocardial infarction (AMI) that were admitted during the first semester of 1991 at the Intensive Care Unit of the Provincial Hospital of Santa Clara were studied. Selvester's score was applied to these patients aimed at showing its usefulnes in the daily clinical practice. The average age of the series was 64 ± 12 and it was observed a predominance of males. None of the clinical conditions considered as risk markers to develop an AMI > 24% according to Selvester's score were associated with this finding. The above scoring system was significantly related to the appearance of some complications during the AMI evolution from the statistical point of view: heart insufficiency (RR = 4.77; CI = 2.94 - 7.73; p= ,0000002), cardiogenic shock (RR = 18.08; CI = 4.26 - 76.65; P = ,0000138), death at the ICU (RR = 9.04; CI = 3.13 -26.14; p = ,0001103). This scoring system may be used in the predicition of complications and fatal outcome during the hospitalization of patients with AMI.